Martial Arts and Combat Sports in numbers: an exploratory overview on numeric or statistical data in Portugal - Vítor Rosa (Universidad de León, 2012)
Anyone who wishes to study martial arts or combat sports in Portugal is almost obliged to obtain numerical or statistical information. However, we should consider that statistics, whatever the situation, are not an objective reality. For the users its fundamental to be aware of the need to obtain a maximum control over the statistics production processes: who have produce them, with what objectives and the purpose scope. In this work we intend to identify, analyse and reflect over the principal numerical or statistical data produced by different entities over the subject of martial arts or combat sports in Portugal. The results obtained show that martial-sportive modalities have been grown in practitioners number, and that the available data are very irregular and, sometimes, confused. After all, the absence of data appears as a semiotic sign of disease and dysfunction in its organization.